Evaluation of HASTE T2 weighted image with reduced echo time for detecting focal liver lesions in patients at risk of developing hepatocellular carcinoma. Issue 157 (December 2022) - Han, Seungchul; Lee, Jeong Min; Kim, Se Woo; Park, Sungeun; Nickel, Marcel Dominik; Yoon, Jeong Hee
Highlights: HASTE-DL showed the highest image quality followed by HASTE-CS and conventional T2WI. HASTE-DL showed superior diagnostic performance to conventional T2WI for detecting LR-4, -5, -M lesions. HASTE-DL did not show difference compared to DWI for detecting LR-4, -5, -M lesions whereas T2WI showed lower sensitivity. Abstract: Purpose: To compare the image quality and performance of half-Fourier acquisition single-shot turbo spin echo (HASTE) sequences, using compressed sensing (HASTE-CS) and deep-learning based reconstruction (HASTE-DL) in detecting focal liver lesions (FLLs), to those of T2-weighted image using BLADE sequence (T2WI) in patients at risk of developing hepatocellular carcinoma (HCC). Materials and methods: This retrospective study included patients at risk of developing HCC who underwent liver MRI including HASTE-DL, HASTE-CS, T2WI and DWI between January and June 2020. Three radiologists independently reviewed the image quality along with FLL detection in the three T2-based sequences and DWI. Reference lesion characterization was done using the complete set of MRI sequences according to the Liver Imaging Reporting and Data System (LI-RADS) v2018. Results: A total of 227 patients with 88 of whom had FLLs (n = 194, mean size 11.7 ± 10.9 mm) were included. HASTE-DL yielded the highest overall image quality, followed by HASTE-CS and T2WI (3.4 ± 0.5, 3.1 ± 0.6, 2.4 ± 0.5, respectively, P < 0.001 for all). In the detection of FLLs, HASTE-DL showed significantly higher sensitivity than T2WI (51.5 % vs 43.6 %, P = 0.007) whereas HASTE-CS and T2WI bore respectively little difference ( P > 0.017) on per-patient basis. For LR-4, -5, -M lesions, HASTE-DL had significantly higher figure of merit than that of T2WI (0.58 vs 0.52, P < 0.001) in per-lesion basis. Conclusion: HASTE-DL demonstrated better image quality and higher performance for FLL detection than conventional T2WI in patients at risk of developing HCC.